The effect of face masks on confusion of emotional expressions - Andrea R. Libby; Collin Scarince (PLoS ONE, 2025)
While the use of personal protective equipment protects healthcare workers against transmissible disease, it also obscures the lower facial regions that are vital for transmitting emotion signals. Previous studies have found that face coverings can impair recognition of emotional expressions, particularly those that rely on signals from the lower regions of the face, such as disgust. Recent research on the individual differences that may influence expression recognition, such as emotional intelligence, has shown mixed results. In the current investigation, we conducted two experiments to build on previous work to further investigate the role of emotional intelligence in emotion recognition. Participants viewed a set of masked and unmasked models displaying six different emotional expressions for a limited time (0.5 s, 1.0 s, or 1.5 s in Experiment 1 and 1.0 s in Experiment 2). Participants then indicated which emotion options they felt each model expressed. Participants’ emotional intelligence was measured using the Schutte Self Report Emotional Test. Emotion recognition accuracy was lower for images with masks than images without masks in both experiments. Confusion rates were not uniform: masked disgust and sadness had the greatest increase of confusion from their unmasked conditions, happiness and surprise had the least confusion in all conditions, and both fear and anger had generally low recognition in masked and unmasked conditions. Emotional intelligence only impacted accuracy when view time was particularly restricted and parts of the face were covered. These results replicate the finding that face masks impair the transmission of emotional signals, and the impairments are a function of the occluded facial regions. Emotional intelligence may moderate this effect in dynamic social interactions where emotional expressions are brief and ambiguous.